31-VIII-Święto Solidarności: nasze święto [ulotka] . 31 August - Solidarity day: our day. Flier - Solidarność Walcząca. (Solidarność Walcząca, 1983)
B&w print on white paper in two columns. Flier, with Solidarność Walcząca logotype (letters "s" and "w" merged) appeals for joining the street protests on the third anniversary of the founding of Solidarity (31 August 1980), under the slogans: "freedom for the imprisoned", "work for society", "self-government, solidarity, independence", as well as presents the program of the alternative festivities.